NOVAS GEOPOLÍTICAS, IGREJAS E POPULAÇÃO SEM RELIGIÃO: ANARQUIA RELIGIOSA NO BRASIL? - Santos, Alberto Pereira dos (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2013)
This article represents a synthesis of our doctoral thesis in human geography, defended at the University of São Paulo. What are the relationships between geopolitics and religion? Our hypothesis held that churches make use of geopolitics to maintain and expand the "religious capital". On the other hand, the geographical analysis of the Brazilian reality identifies a slow and fruitful process of metamorphosis of beliefs and spiritual emancipation through the growth of the religious population without religion. This process occurs without the government of the churches. Based on the ideas of geoethic and mutual support, it is argued that the existence of the population without religion represents religious anarchy in Brazil.